HANDBOOK of mixed methods in social & behavioral research / editor Abbas Tashakkori, Charles Teddlie ; penerjemah Daryatno ; penyunting Saifuddin Zuhri Qudsy. - Abbas Tasakkori; Charles TEddlie; Daryatno; Saifuddin Zuhri Qudsy (Pustaka Pelajar, 2010)
xii, 662 hlm. : ilus. ; 28 cm